Social régulation and medias values - عبد القادر دريدي, (International Journal of Social Communication, 2020)
This article is devoted to the efforts of professor Jean-Claude Bertrand as one of the pioneers in the field of media ethics and deontology, who has done much to promote the media and ensure respect for the notion of public service. We try, through this article, not only to present the hard work of Mr. Jean-Claude Bertrand which is unknown in Algeria as like as all the Arab world, but also try to Approximate between the theory of social responsibility and the determinism and values theory. This latter, which, despite its overwhelming scientific arguments, Need practical mechanisms. Although this process is risky because of the different cultural references behind each theory, we will seek to ensure this transition and to ensure that the theory of determinism and value benefits from advances in the theory of social responsibility